A new alternating group explicit-implicit algorithm with high accuracy for dispersive equation - 张青洁 王文洽 (Applied mathematics and mechanics, 2008)
In this paper, a new alternating group explicit-implicit （nAGEI） scheme for dispersive equations with a periodic boundary condition is derived. This new unconditionally stable scheme has a fourth-order truncation error in space and a convergence ratio faster than some known alternating methods such as ASEI and AGE. Comparison in accuracy with the AGEI and AGE methods is presented in the numerical experiment.